STRATEGI PEMASARAN ISLAMI DENGAN MEDIA SOSIAL UNTUK MENINGKATKAN PENJUALAN PRODUK - Aprilia Dian Evasari (Istithmar: Jurnal Studi Ekonomi Syariah, 2020)
The rise of promotions and buying-selling through internet where social media has become one of the media, it has many positive impacts, such as buying-selling transactions have become easier. The purpose of this study was to find out and analyze the role of social media in supporting the marketing of Micro, Small, and Medium Enterprises (MSME) product “Kirana”in Tales Village, Ngadiluwih, Kediri. The research method used is a qualitative method with a descriptive exploratory approach, meaning that the data obtained from both the researcher, key informants and existing data are then analyzed. The sharia marketing strategy implemented by MSME “Kirana” which prioritizes sharia elements brings a lot of blessings, this has a big impact on the increase in consumer response and blessed profit. From the results of the study, it was found that the role of social media is very helpful in marketing products produced by MSME “Kirana” and increase sales figures. The results of this study indicate that the use of social media as a promotion of MSME “Kirana” market using several social media such as: WA (Whatsapp), Instagram, FB (Facebook). Those social media WA ( Whatsapp) used as a means for ordering, Facebook and Instagram used for uploading photos of the items they sell. Those social media give a positive impact, namely their sales have increased which is in accordance with the function of social media in trading, which can increase sales.